Navigating Generational Change: The Role of Leadership Skills in Sustaining Family Businesses in Indonesia - Harijadi, Bambang Dwi; Suhariadi, Fendy; Suparto Wijoyo; Sinaga, Eduard; Muhaimin, Hikmah (Technium Social Sciences Journal, 2024)
A 2014 PwC survey reported that 60% of the next generation is involved in senior executive roles within family businesses, and 27% are present in the company but not as senior executives. The survey also indicated that 37% of family businesses extend up to the second generation, and 33% reach the third generation. This highlights a phenomenon in Indonesia—the lack of sustainability of family businesses across multiple generations. While acknowledging the importance of accounting, management, and internal control, effective leadership in the succeeding generation can further ensure the sustainability of a family business. Therefore, it is crucial for the preceding generation to engage in efforts to acquire or prepare for such leadership. The paradox concerning the importance of the next generation in family businesses is seen as a fundamental phenomenon for developing specific hypotheses with reference to the relationship between leadership, organizational change capability, and the sustainability of family businesses. This enables these businesses to continue thriving and expanding. This study aims to identify and analyze the rules and relationships between skills, the capability of change, and the economic sustainability of family businesses in Indonesia. Utilizing a quantitative approach with an explanatory study design, the research concludes that the impact of leadership skills on the economic sustainability of family businesses, the effect of change capability on economic sustainability, and the moderating role of change capability on the relationship between leadership skills and economic sustainability are all significant, albeit at varying levels of significance. The indirect influence of leadership skills on economic sustainability through change capability is also significant, though minimal. When change capability acts as a moderator, it is proven to strengthen the relationship between economic sustainability and leadership skills.